Kandungan dan Kecernaan Bahan Kering Bahan Organik Isi Rumen Sapi Bali Timor secara In Vitro Pada Dua RPH Berbeda - Tahun, Maria; Hilakore, Maritje A.; Nenobais, Mariana; Lawa, Emma D. Wie (Animal Agricultura, 2025)
This study aims to determine the content and digestibility of the rumen contents of Bali Timor cattle at two different Slaughterhouses (RPH), Bimoku and Aldia, Kupang, using in vitro methods. The research employed an experimental method designed with an analysis using the T-test (comparison test). A total of 15 female Bali Timor cattle from each slaughterhouse were used as replicates (n). The variables observed were the content and digestibility of dry matter (DM) and organic matter (OM). Data were analyzed using the independent sample t-test at a 5% significance level to compare the rumen contents quality of RPH Bimoku and RPH CV Aldia. The T-test results showed that the dry matter (DM) content at RPH CV Aldia was significantly (p > 0.05) higher than that at RPH Bimoku; organic matter (OM) at RPH CV Aldia was highly significant (p > 0.01) higher than that at RPH Bimoku; the digestibility of dry matter (DMD) and organic matter (OMD) at RPH CV Aldia was highly significant (p > 0.01) higher than that at RPH Bimoku. It is concluded that the difference in slaughterhouse location causes differences in the content of dry matter, organic matter, and their digestibility in the rumen contents of Bali Timor cattle.